Physicochemical and functional performance of pectin extracted by QbD approach from Tamarindus indica L. pulp. (10th December 2015) - Sharma, Radhika; Kamboj, Sunil; Khurana, Rajneet; Singh, Gursharan; Rana, Vikas
Highlights: A QbD approach for extraction of tamarind pectin (TP) from Tamarindus indica L. pulp. Role of polarity index in the extraction of TP identified. Equilibrium moisture content and wetting time suggested its pharmaceutical benefits. An increase in antioxidant activity of TP suggested alternative to apple pomace, citrus and commercial pectin. Abstract: The aim of present investigation was to utilize quality by design (QbD) approach for extraction of tamarind pectin (TP) from Tamarindus indica L. pulp employing purity descriptors as indicator. The software generated quadratic equations showed significant effect of polarity index as compared to pulp concentration and boiling temperature on percentage yield and purity characteristics of TP. An insignificant effect on purity descriptors and percentage yield of TP upon replacement of acetone with methanol during predicted vs observed correlation studies (being similar polarity index of 5.1) pointed towards overwhelming influence of solvent polarity. Further, the FTIR-ATR, 1 H NMR, DSC and mass spectroscopy suggested TP was rhamnogalacturonan pectin with no tartaric acid content. TP was found to have significantly higher antioxidant activity as compare to apple pomace pectin, citrus peel pectin and commercial pectin. Overall, the physicochemical properties and antioxidant potential of TP could be utilized as an excipient for food and pharmaceutical industry.